Adoptive Cell Therapy in Breast Cancer: A Current Perspective of Next-Generation Medicine - Fuentes-Antrás, Jesús; Guevara-Hoyer, Kissy; Baliu-Piqué, Mariona; García-Sáenz, José Ángel; Pérez-Segura, Pedro; Pandiella, Atanasio; Ocaña, Alberto (Frontiers in Oncology, 2020)
Immunotherapy has become a cornerstone in the treatment of cancer and changed the way clinicians and researchers approach tumor vulnerabilities. Durable responses are commonly observed with immune checkpoint inhibitors in highly immunogenic tumors, while the infusion of T cells genetically engineered to express chimeric antigen receptors (CARs) has shown impressive efficacy in certain types of blood cancer. Nevertheless, harnessing our own immunity has not proved successful for most breast cancer patients. In the era of genomic medicine, cellular immunotherapies may provide a more personalized and dynamic tool against tumors displaying heterogeneous mutational landscapes and antigenic pools. This approach encompasses multiple strategies including the adoptive transfer of tumor-infiltrating lymphocytes, dendritic cells, natural killer cells, and engineered immune components such as CAR constructs and engineered T cell receptors. Although far from permeating the clinical setting, technical advances have been overwhelming in recent years, with continuous improvement in traditional challenges such as toxicity, adoptive cell persistence, and intratumoral trafficking. Also, there is an avid search for neoantigens that can be targeted by these strategies, either alone or in combination. In this work, we aim to provide a clinically-oriented overview of preclinical and clinical data regarding the use of cellular immunotherapies in breast cancer.